Legislative disconnect or institutional gatekeeping? Challenges of researching South Africa’s military past - Kleynhans, Evert; Gordon, Will (Scientia Militaria - South African Journal of Military Studies, 2020)
The Department of Defence Archive in Pretoria is the repository of all military documents generated by the Union Defence Force, the South African Defence Force and the South African National Defence Force. This makes it the foremost source of primary information for researchers of South African military history. However, an almost total ban on access to archival documents from 1 January 1970 onwards complicates research into later periods. In fact, anyone researching post-1970 military-related topics has to apply for access to archival documents through the Promotion of Access to Information Act. The traditional weapon in the armoury of the historian – the systematic trawling of archives – is thereby negated, while the methodology of post-1970 historical research differs significantly from commonly accepted historical practices. Finding aids, the only access route to classified information in this analogue archive, offer only the briefest descriptions of the content of files, and researchers need almost esoteric intuition to identify documents that are even remotely relevant to their research. Additionally, a fee is payable for declassification, and the process can take several months to complete. This review article reports on the theoretical workings of the Promotion of Access to Information Act, and uses an actual research example as a case study to illustrate the practical implications of conducting research at the Department of Defence Archive in South Africa based on classified military documentation.